2021
DOI: 10.3847/1538-3881/abccc6
|View full text |Cite
|
Sign up to set email alerts
|

TESS Hunt for Young and Maturing Exoplanets (THYME). IV. Three Small Planets Orbiting a 120 Myr Old Star in the Pisces–Eridanus Stream*

Abstract: Young exoplanets can offer insight into the evolution of planetary atmospheres, compositions, and architectures. We present the discovery of the young planetary system TOI 451 (TIC 257605131, Gaia DR2 4844691297067063424). TOI 451 is a member of the 120-Myr-old Pisces-Eridanus stream (Psc-Eri). We confirm membership in the stream with its kinematics, its lithium abundance, and the rotation and UV excesses of both TOI 451 and its wide binary companion, TOI 451 B (itself likely an M dwarf binary). We identified … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 184 publications
(180 reference statements)
1
27
0
Order By: Relevance
“…In the meantime, several of these (C)TOIs, which were revealed as members of multiple star systems in the course of our survey, could already be confirmed by follow‐up observations to be exoplanet host stars, e.g. TOI 451, 1098, 1259, and 1333 (Martin et al 2021; Newton et al 2021; Rodriguez et al 2021; Tofflemire et al 2021).…”
Section: Introductionsupporting
confidence: 74%
“…In the meantime, several of these (C)TOIs, which were revealed as members of multiple star systems in the course of our survey, could already be confirmed by follow‐up observations to be exoplanet host stars, e.g. TOI 451, 1098, 1259, and 1333 (Martin et al 2021; Newton et al 2021; Rodriguez et al 2021; Tofflemire et al 2021).…”
Section: Introductionsupporting
confidence: 74%
“…The TESS mission (Ricker et al 2015) provides a new opportunity for targeted searches of young exoplanets from precise time-series photometry for millions of targets across most of the sky. For example, the THYME survey has identified several planets in known young associations spanning a diversity of Galactic environments, such as the Tucana-Horologium and Ursa Major moving groups (Newton et al 2019;Mann et al 2020), the Scorpius-Centaurus OB association (Rizzuto et al 2020), the Pisces-Eridanus stream (Newton et al 2021), and even a previously unknown association (Tofflemire et al 2021). Other searches of TESS data have revealed planets orbiting young stars in the IC 2602 cluster (Bouma et al 2020) and in the field (Zhou et al 2021).…”
mentioning
confidence: 99%
“…The number of known young transiting planets has grown significantly in recent years (e.g., Obermeier et al 2016;David et al 2018;Benatti et al 2019;Newton et al 2021). This growth was primarily driven by a combination of the K2 and TESS missions surveying nearby young clusters and star-forming regions (Ricker et al 2014;Van Cleve et al 2016), improvements in filtering variability in young stars (e.g., Aigrain et al 2016;Rizzuto et al 2017), and more complete identification of young stellar associations from Gaia kinematics (e.g., Cantat-Gaudin et al 2018;Kerr et al 2021).…”
mentioning
confidence: 99%
“…As part of the TESS Hunt for Young and Maturing Exoplanets survey (THYME; Newton et al 2019), our team searches TESS data using a specialized pipeline in order to identify young planets missed by standard searches (e.g., Rizzuto et al 2020), and checks previously-identified planet candidates for signs of membership in a young association (e.g., Newton et al 2021;Mann et al 2020). We identified TOI 1227 (2MASS J12270432-7227064, TIC 360156606) as a member of a young association, with a planet candidate (TOI1227.01) identified by the TESS mission, and astrometry consistent with membership in the Lower Centaurus Crux (LCC) region of the Scorpius-Centaurus (Sco-Cen) OB association (Goldman et al 2018;Damiani et al 2019).…”
mentioning
confidence: 99%